Sex and Response to Cardioprotective Conditioning Maneuvers - Querio, Giulia; Geddo, Federica; Antoniotti, Susanna; Gallo, Maria Pia; Penna, Claudia (Frontiers in Physiology, 2021)
Ischemic heart disease (IHD) is a multifactorial pathological condition strictly related to genetic, dietary and lifestyle factors. Its morbidity and mortality rate represents one of the most important pathological issue that today involves younger people in a stronger way than in the past. IHD clinical outcomes are difficult to treat and have a high economic impact on health care. So, prevention of this pathological condition through cardioprotective manoeuvres represents the first line of intervention, as already underlined by several animal and human studies. Even if time of intervention is important to prevent severe outcomes, many studies highlight that sex-dependent responses are crucial for the result of cardioprotective procedures. In this scenario sexual hormones have revealed an important role in cardioprotective approach, as women seem to be more protected towards cardiac insults when compared to male counterparts. Aim of this minireview is to show the molecular pathways involved in cardioprotective protocols and to elucidate how sexual hormones can contribute in ameliorating or worsening the physiological responses to IHD.